Intracontinental deformation in central Asia: Distant effects of India – Eurasia convergence revealed by apatite fission-track thermochronology - De Grave, Johan; Buslov, Michael M; Van Den Haute, Peter (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 121-2